Orbital Gating Driven by Giant Stark Effect in Tunneling Phototransistors. Issue 6 (22nd December 2021) - Kim, Eunah; Hwang, Geunwoo; Kim, Dohyun; Won, Dongyeun; Joo, Yanggeun; Zheng, Shoujun; Watanabe, Kenji; Taniguchi, Takashi; Moon, Pilkyung; Kim, Dong‐Wook; Sun, Linfeng; Yang, Heejun
Abstract: Conventional gating in transistors uses electric fields through external dielectrics that require complex fabrication processes. Various optoelectronic devices deploy photogating by electric fields from trapped charges in neighbor nanoparticles or dielectrics under light illumination. Orbital gating driven by giant Stark effect is demonstrated in tunneling phototransistors based on 2H‐MoTe2 without using external gating bias or slow charge trapping dynamics in photogating. The original self‐gating by light illumination modulates the interlayer potential gradient by switching on and off the giant Stark effect where the d z 2‐orbitals of molybdenum atoms play the dominant role. The orbital gating shifts the electronic bands of the top atomic layer of the MoTe2 by up to 100 meV, which is equivalent to modulation of a carrier density of 7.3 × 10 11 cm –2 by electrical gating. Suppressing conventional photoconductivity, the orbital gating in tunneling phototransistors achieves low dark current, practical photoresponsivity (3357 AW –1 ), and fast switching time (0.5 ms) simultaneously. Abstract : Orbital gating is introduced driven by giant Stark effect in tunneling phototransistors based on 2H‐MoTe2 without using external gating bias or slow charge trapping dynamics in conventional photogating, which realizes low dark current, practical photoresponsivity, and fast switching time simultaneously.